An anonymous girl - Hendricks, Greer; Pekkanen, Sarah (St. Martin's Press, 2019)
"When Jessica Farris signs up for a psychology study conducted by the mysterious Dr. Shields, she thinks all she'll have to do is answer a few questions, collect her money, and leave. But as the questions grow more and more intense and invasive and the sessions become outings where Jess is told what to wear and how to act, she begins to feel as though Dr. Shields may know what she's thinking...and what she's hiding."--